2021
DOI: 10.1371/journal.pone.0257976
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HER2 overexpression and amplification in cervical cancer: A systematic review and meta-analysis

Abstract: The reported rates of HER2 positivity in cervical cancer (CC) range from 0% to 87%. The importance of HER2 as an actionable target in CC would depend on HER2 positivity prevalence. Our aim was to provide precise estimates of HER2 overexpression and amplification in CC, globally and by relevant subgroups. We conducted a PRISMA compliant meta-analytic systematic review. We searched Medline, EMBASE, Cochrane database, and grey literature for articles reporting the proportion of HER2 positivity in CC. Studies asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…This confirms similar observations recently made in a larger cohort of HPVA not restricted to cases with metastatic disease 10 . In concordance with prior studies, we also identified two patients in group 2 with tumours showing ERBB2 amplification, highlighting the value of evaluating for this targetable genetic alteration in cervical adenocarcinomas when clinically indicated 32 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This confirms similar observations recently made in a larger cohort of HPVA not restricted to cases with metastatic disease 10 . In concordance with prior studies, we also identified two patients in group 2 with tumours showing ERBB2 amplification, highlighting the value of evaluating for this targetable genetic alteration in cervical adenocarcinomas when clinically indicated 32 …”
Section: Discussionsupporting
confidence: 92%
“…10 In concordance with prior studies, we also identified two patients in group 2 with tumours showing ERBB2 amplification, highlighting the value of evaluating for this targetable genetic alteration in cervical adenocarcinomas when clinically indicated. 32 From a clinical outcome perspective, patients with pattern A HPVA/AIS and ovarian involvement in our cohort did well: all were free of disease with median follow-up of 53 months. This contrasts with the adverse outcome frequently seen in patients with pattern B/C HPVA and metastatic disease.…”
Section: Discussionmentioning
confidence: 75%
“… 31 , 32 , 33 Furthermore, human EGFR2 (HER2) mutations and amplifications were observed in 3%-6% and 1%-12% of CC, respectively, and were also correlated with a worse prognosis. 34 Although EGFR inhibition seemed a promising target in CC treatment, several phase II studies evaluating EGFR inhibitors such as cetuximab, gefitinib, erlotinib, or lapatinib showed only limited activity. 27 , 35 , 36 , 37 Neratinib was explored in the phase II SUMMIT trial including 16 patients (62.5% of ADK) with HER2-mutated recurrent CC progressing after platinum-based treatment.…”
Section: Epidermal Growth Factor Receptor Inhibitorsmentioning
confidence: 99%
“…Furthermore, our study showed that HER2 was not expressed in patients with squamous cell histology, whereas HER2 2+ and 3+ were identified in patients with non-squamous histology. Previous studies have indicated that a small, yet meaningful, proportion of patients with cervical cancer overexpress the HER2 receptor ( 19 , 20 ). In our study, two patients overexpressing HER2 received T-DXd and showed a good response considering the treatment setting.…”
Section: Discussionmentioning
confidence: 99%